Art and phenomenology - Parry, Joseph D. (London ; New York : Routledge, 2011)
1. The phenomenological relevance of art / Mark Wrathall -- 2. Phenomenology and aesthetics; or, why art matters / Steven Crowell -- 3. Objectivity and self-disclosedness: the phenomenological working of art / Jeff Malpas -- 4. Horizon, oscillation, boundaries: a philosophical account of Mark Rothko?s art / Violetta L. Waibel -- 5. Representing the real: a Merleau-Pontyan account of art and experience from the Renaissance to New Media / Sean Dorrance Kelly -- 6. The judgment of Adam: self-consciousness and normative orientation in Lucas Cranach's Eden / Wayne Martin -- 7. Describing reality or disclosing worldhood?: Vermeer and Heidegger / Beatrice Han-Pile -- 8. Phenomenological history, freedom, and Botticelli's Cestello Annunciation / Joseph D. Parry -- 9. Showing and seeing: film as phenomenology / John B. Brough.
Includes bibliographical references and index.
boek